The Preacher' as Scientist - Johnstone, William (Scottish journal of theology, 1967)
The aim of this paper is to contribute, if possible, a little towards the understanding of the Book of Ecclesiastes, or The Preacher, and to illuminate something of the contemporary significance of its contents. The paper is prompted too by a feeling of dissatisfaction at the negativity with which much of modern writing on Ecclesiastes is tinged, and by the conviction that if Koheleth, the Preacher, is once granted a sympathy of interpretation, and the forcefulness and novelty of his expression are recognised, his message can be seen to be apposite and telling.1